On the Architectural Solutions of Medium and Multi-Storey Experimental Courtyard Residences - Inogomov, Bakhtiyor Ismailovich; Mirkamol ugli, Sodikov Mirasrol (European Journal of Life Safety and Stability (2660-9630), 2022)
This article is about a brief classification of medium and high-rise pile residential buildings built as an experiment in our country.